Hyperammonemia presenting as opsoclonus–myoclonus–ataxia–tremor syndrome: A case report - Sandhya Manorenj; Govind Verma (Annals of Movement Disorders, 2022)
Opsoclonus myoclonus syndrome (OMS) is a rare autoimmune condition occurring due to Purkinje cell degeneration due to remote aetiology. Most often it occurs as a paraneoplastic syndrome. Here we report a case of opsoclonus-myoclonus–ataxia tremor syndrome in a 60-year-old woman that occurred due to hyperammonemia and she recovered completely with immunotherapy and correction of hyperammonemia. OMS is the first in literature associated with hyperammonemia.